On the changes in the main mineral constituents of Baltic herring fillets while standing in saline solutions - Kuusi, Taina; Kytökangas, Riitta (Agricultural and Food Science, 1970)
The purpose of this investigation was to find out what changes take place in the quantities of the ash components of Baltic herring fillets, such as alkali and alkaline earth metals, chloride and phosphate, when the fillets are kept in chloride and phosphate solutions. It was hoped that these experiments might give information on the nature of the protective effect of phosphate, as it is capable of preventing harmful changes in the myofibrillar proteins, caused by NaCl solution. The standing solutions were 3 % NaCl, 1 % Na pyrophosphate, and a solution containing both these salts. The fillets were investigated at the beginning and after a storage of 1 and 5 days. The total ash, Na, K, Mg, Ca, Cl, and P was analyzed in the fillets. The original values obtained were compared with the values given for Baltic herring and herring in the literature, as far as such data were available. The Na and Cl values of Baltic herring obtained here were somewhat lower than those reported for herring. The values obtained for K, Ca and P are somewhat high, but still the values in general agree in range with the values in the literature. Storage in the solutions increased the values of ash, even if this increase in regard to the pyrophosphate solution was only stated if the ash values were calculated for the original weights of the fillets. As far the metals were concerned, the amount of Na increased in all cases, as both chloride and pyrophosphate were used as Na salts. By contrast, the amount of K was considerably decreased, the amount of Mg less and that of Ca still less. The loss of K and Mg continued progressively for the whole standing period, while the amount of Ca returned towards the original value after a decrease during the first day. With all the metals the size of the change depended on the strength of the standing solution. The amount of chloride in the fillets was increased if storage took place in solutions containing NaCl; immigration of Cl was independent of the presence of pyrophosphate. Pyrophosphate alone extracted Cl from the fillets almost completely. The amount of phosphate in the fillets was again decreased in all the solutions, the decrease being greatest when the standing solution contained no phosphate; even then, the fillets still retained approx. 23 % of the original P. When the standing solution contained phosphate, the loss of P was small and independent of the presence of chloride. When the metals and anions investigated were calculated as equivalents, it was stated that in all cases there was an excess of cations in the fillets. During standing, changes took place in the cation excess. When standing in pyrophosphate solution alone, a small progressive increase of the cation excess was observable, while when standing in NaCl solution alone, the cation excess first decreased strongly and then partly returned towards the original value. If the solution in addition contained also pyrophosphate, the decrease was much less noticeable. In this respect the pyrophosphate has clearly inhibited the effect of NaCl, and this may be connected with the influence of pyrophosphate protecting the myofibrillar proteins.